Inclusion Process in a Regular School of Education in the City of Nova Olinda-Ceará (Research, Society and Development, 2021)
This paper focuses on the inclusion of students with special needs in the teaching-learning process in the school context of regular education. It configures a reflection on inclusive education, making a brief analysis of the history of the process of including these children in school. Thus, this is a bibliographic research whose main theme was to discuss the challenge of inclusion in the school environment, and the reorganization of special education and reflecting on the importance of teacher education that contributes to the development of an education that respects diversity. To approach the historical trajectory of the education of people with special educational needs, from the segregative attendances to the inclusive processes, presenting some concepts necessary for the understanding of what is special education and about how are identified frames that constitute subjects attended by the special education. The results indicate that the specialized educational service has the function of identifying, elaborating and organizing pedagogical and accessibility resources that eliminate the barriers to the full participation of the students, considering their specific needs.